Performance of Native Florida Plants under North Florida Conditions - Jeffrey G. Norcini; James H. Aldrich (EDIS)
ENH-1074, a 22-page illustrated fact sheet by Jeffrey Norcini and James H. Aldrich, provides results of a study evaluating 15 cultivars of native wildflowers for performance in North Florida landscape conditions in Quincy, FL. Includes description, performance, and graph of appearance rating throughout the year for each wildflower. Published by the UF Department of Environmental Horticulture, November 2007.